Sonographic review of thyroid lesion based on ATA and ACR-tirads classification - Nagalindam, Deivind Kumar (2021)
Background: Thyroid malignancy is one of the commonest cancers among adults with prevalence rate of 3-7%. High frequency ultrasound has been gold standard in detecting thyroid nodules and able to stratify malignant lesions. Research has been undertaken on these nodules with qualitative and quantitative manners to stratify these lesions. The purpose of this study is to compare stratification of thyroid lesions based on ACR-TIRADS and ATA in detecting malignant thyroid nodules and analyse the sensitivity and specificity of each scoring system. Methods: A retrospective case-control study using sonographic images done prior to the patient's thyroidectomy. Identified thyroid nodules were analysed using ATA and ACR-TIRADS classification system for stratification and scoring. Variables such as age, gender, family history, previous malignancy history and previous irradiation history were documented in data collection form. For the purpose of our study, ATA benign and very low suspicion nodule were categorized as benign and TR2 and below category was taken as benign. On contrary to this, ATA low suspicion nodule with ACR-TIRADS TR3 category and above were taken as malignant. Results: A total of 129 nodules from 53 participants were included in this study. The mean total identified benign thyroid nodule based on USG ATA classification showed 0% benign and 3% were malignant on HPE. Meanwhile, based on benign USG ACR-TIRADS features, 0.8% were benign and 3.9% were malignant. Malignant thyroid HPE based on ATA and ACR-TIRADS classification was 93.0% and 91.0% respectively. The specificity, NPV (Negative predictive value) and accuracy of ACR- TIRADS classification were high (95.2%, 97.6% and 93.0%) respectively. There was no significant association of each sonographic characteristics ACR-TIRADS with HPE proven malignant thyroid nodules. A total of 28 nodules of category TR3(TIRADS 3) was identified as HPE (Histopathological examination) proven malignancy with malignancy rate of 21.71%. in comparison to TR4 nodule and TR5 nodule of 10.08 % and 6.98% of detected malignancy rate. Conclusion: Overall, this study showed that no single sonographic features of thyroid nodule have significant association with malignant histology outcome of thyroid nodule. However, combination of sonographic features improves predictability of malignancy. Concisely, ACR-TIRADS is simple and practical method for thyroid nodule stratification with high accuracy.